# Evaluation of expressions

If a

(i)a

(ii) a

^{2}-3a+1=0, find(i)a

^{2}+1/a^{2}(ii) a

^{3}+1/a^{3}**Result****Leave us a comment of this math problem and its solution (i.e. if it is still somewhat unclear...):**

**Showing 0 comments:**

**Be the first to comment!**

#### To solve this verbal math problem are needed these knowledge from mathematics:

## Next similar math problems:

- Expressions 3

If k(x+6)= 4x^{2}+ 20, what is k(10)=? - Algebra

X+y=5, find xy (find the product of x and y if x+y = 5) - Expression with powers

If x-1/x=5, find the value of x^{4}+1/x^{4} - Quadratic equation

Find the roots of the quadratic equation: 3x^{2}-4x + (-4) = 0. - Square root 2

If the square root of 3m^{2}+22 and -x = 0, and x=7, what is m? - Solve equation

solve equation: ? - Difference AP 4

Calculate the difference of the AP if a1 = 0.5, a2 + a3 = -1.1 - Crystal water

The chemist wanted to check the content of water of crystallization of chromic potassium alum K_{2}SO_{4}* Cr_{2}(SO_{4}) 3 * 24 H_{2}O, which was a long time in the laboratory. From 96.8 g of K_{2}SO_{4}* Cr_{2}(SO_{4}) 3 * 24 H_{2}O prepared 979 cm^{3}solution of base. S - Roots

Determine the quadratic equation absolute coefficient q, that the equation has a real double root and the root x calculate: ? - Discriminant

Determine the discriminant of the equation: ? - Equation

Equation ? has one root x_{1}= 8. Determine the coefficient b and the second root x_{2}. - Solve 3

Solve quadratic equation: (6n+1) (4n-1) = 3n^{2} - Reciprocal equation 2

Solve this equation: x + 5/x - 6 = 4/11 - Variation equation

Solve combinatorics equation: V(2, x+8)=72 - Tubes

Iron tubes in the warehouse are stored in layers so that each tube top layer fit into the gaps of the lower layer. How many layers are needed to deposit 100 tubes if top layer has 9 tubes? How many tubes are in bottom layer of tubes? - Quadratic equation

Quadratic equation ? has roots x_{1}= -26 and x_{2}= -86. Calculate the coefficients b and c. - Theorem prove

We want to prove the sentence: If the natural number n is divisible by six, then n is divisible by three. From what assumption we started?